Uncovering the wide protective responses in Coffea spp. leaves to single and superimposed exposure of warming and severe water deficit - Rodrigues, Ana P.; Pais, Isabel P.; Leitão, António E.; Dubberstein, Danielly; Lidon, Fernando C.; Marques, Isabel; Semedo, José N.; Rakocevic, Miroslava; Scotti-Campos, Paula; Campostrini, Eliemar; Rodrigues, Weverton P.; Simões-Costa, Maria Cristina; et al. (Frontiers in Plant Science, 2024)
Climate changes boosted the frequency and severity of drought and heat events, with aggravated when these stresses occur simultaneously, turning crucial to unveil the plant response mechanisms to such harsh conditions. Therefore, plant responses/resilience to single and combined exposure to severe water deficit (SWD) and heat were assessed in two cultivars of the main coffee-producing species: Coffea arabica cv. Icatu and C. canephora cv.Conilon Clone 153 (CL153). Well-watered plants (WW) were exposed to SWD under an adequate temperature of 25/20 °C (day/night), and thereafter submitted to a gradual increase up to 42/30 °C, and a 14-d recovery period (Rec14). Greater protective response was found to single SWD than to single 37/28 °C and/or 42/30 °C (except for HSP70) in both cultivars, but CL153-SWD plants showed the larger variations of leaf thermal imaging crop water stress index (CWSI, 85% rise at 37/28 °C) and stomatal conductance index (I G , 66% decline at 25/20 °C). Both cultivars revealed great resilience to SWD and/or 37/28 °C, but a tolerance limit was surpassed at 42/30 °C. Under stress combination, Icatu usually displayed lower impacts on membrane permeability, and PSII function, likely associated with various responses, usually mostly driven by drought (but often kept or even strengthened under SWD and 42/30 °C). These included the photoprotective zeaxanthin and lutein, antioxidant enzymes (superoxide dismutase, Cu,Zn-SOD; ascorbate peroxidase, APX), HSP70, arabinose and mannitol (involving de novo sugar synthesis), contributing to constrain lipoperoxidation. Also, only Icatu showed a strong reinforcement of glutathione reductase activity under stress combination. In general, the activities of antioxidative enzymes declined at 42/30 °C (except Cu,Zn-SOD in Icatu and CAT in CL153), but HSP70 and raffinose were maintained higher in Icatu, whereas mannitol and arabinose markedly increased in CL153.Overall, a great leaf plasticity was found, especially in Icatu that revealed greater responsiveness of coordinated protection under all experimental conditions, justifying low PI Chr and absence of lipoperoxidation increase at 42/30 °C. Despite a clear recovery by Rec14, some aftereffects persisted especially in SWD plants (e.g., membranes), relevant in terms of repeated stress exposure and full plant recovery to stresses.